AB1118-HPR Health Professionals' (HPS) Perspectives When Working with People with Rheumatological & Musculoskeletal Disorders (RMDS) and Lower Levels of Health Literacy: A Qualitative Focus Group Study. (15th July 2016) - Adams, J.; Lowe, W.; Armstrong, R.; Russell, C.; Lueddeke, J.; Protheroe, J.; McCaffery, K.; Nutbeam, D.; Ballinger, C.
Abstract : Background: The high prevalence of RMDs and the high proportion of time HPs spend on advising patients with RMDs means that implementing effective self-management strategies is important. Health literacy includes the cognitive and social skills which determine the motivation and ability of individuals to access, understand and use information to promote good health. People with lower health literacy levels have lower levels of activation for self-care and worse functional health outcomes than people with higher levels of health literacy. Objectives: To explore HPs' patient education practice and perspectives when working with patients with RMDs and lower levels of health literacy. Methods: Key contacts from clinics, community GP surgeries and groups identified interested HPs. They were eligible if they had supported patients in developing self-management skills. Participants completed a health literacy questionnaire prior to taking part in a focus group guided by an interview schedule. These were audio-recorded, transcribed and analysed thematically. Results: Five focus group and 2 individual interviews (n=33) were conducted including a consultant rheumatologist; GPs, advance nurse practitioners, nurses, care assistants, occupational therapists, physiotherapists, a podiatrist, a patient advocate, health researchers, a project manager. Key themes included: Experiencing low health literacy as a RMD service provider: whilst HPs generally had not previously considered health literacy as an issue for their patients, most could identify indicators of low health literacy such as difficulty recalling information, adhering to exercises or medication and recurrent healthcare-seeking behaviour. Working with lower health literacy and RMD patients: HPs experienced that patients with lower health literacy had unrealistic expectations of a cure for their RMD pain. This could impact on patient perceptions about the need for ongoing self-management. Delivering patient education: HPs identified that person-centred advice, tailored to the needs of the individual constituted core practice. Time limitations, especially for GPs were the biggest challenge for delivering education. Several practical, educational strategies were in use and identified as relevant for patients with lower health literacy. Strategies to support self-management: different communication modes that did not rely on written material were in use alongside effective interpersonal techniques such as using analogies and metaphors to explain detail. The use of positive and encouraging language was recognised as important. Conclusions: HPs did not have a clear way of identifying patients with low health literacy but used behaviour e.g. poor adherence and repeat appointments as indicators. Patients' perceived unrealistic expectations about a cure for their RMD and pain impacted negatively on their perceptions about self-management. There was evidence for health professionals utilising effective educational and inter-personal strategies as a means of supporting patients with lower health literacy. Acknowledgement: Arthritis Research UK for full funding. Disclosure of Interest: None declared